Sexual orientation discrimination in the cypriot labour market: Distastes or uncertainty? - Nick Drydakis (Institute for the Study of Labor (IZA), 2012)
Sexual orientation and employment bias is examined in Cyprus (Republic of Cyprus: Nicosia, Limassol, Larnaca, Paphos) by implementing an experiment for the period 2010-2011. The design is aimed at answering three main questions: Do gay and lesbian people face occupational access constraints and entry wage bias than comparable heterosexuals? Do gay and lesbian people benefit from providing more job-related information? Does the differential treatment between gay/lesbian and heterosexual applicants disappear as the information of the applicants increases? Methodologically, we sent applications to advertised vacancies and we experimented with two information sets the 'sexual orientation' and 'information' of the potential applicants. The estimations suggest that gay and lesbian applicants face significant bias than heterosexual applicants. Moreover, both heterosexual and gay/lesbian applicants gain by providing more job-related information. However, the estimations suggest that the informational premium for sexual orientation minorities could not reduce the discriminatory patterns. The current results indicate that discrimination against sexual orientation minorities in the Cypriot labour market is a matter of preference, not the result of limited information. One strategy the Cypriot government may employ is to try to affect public opinion and people's attitudes towards sexual orientation minorities. This is the first nationwide field experiment in the Cypriot labour market and contributes to the literature as it is the first field study on sexual orientation which tries to disentangle statistical from taste-based discrimination in the labour market.
Keywords: C93; J7; J82; 330; sexual orientation; hiring discrimination; entry wage offers; taste theory of discrimination; statistical theory of discrimination; Homosexualität; Arbeitsmarktdiskriminierung; Lohndifferenzierung; Zypern